‘[A] Mere Mystery-Man’: Disraeli and the Church of England’s Episcopate - Jérôme Grosclaude (Cahiers Victoriens et Edouardiens)
The truthfulness of Disraeli’s membership of the Church of England has drawn much attention, and his Anglicanism has often been denounced as a mere façade. An alleged evidence of Disraeli’s fake Anglicanism has long been his episcopal appointments (or really recommendations of appointments), and, more broadly, his relations with the episcopate. However, we will see that, even though political calculations were seldom absent, Disraeli’s recommendations generally aimed at striking a balance, and at not unduly upsetting the internal equilibrium of the Established Church.